2018
DOI: 10.15296/ijwhr.2019.35
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Pap Smear and Colposcopy in Non-benign Cervical Lesions

Abstract: Objectives: Cervical cancer is a very common and lethal condition; however, owing to longstanding premalignant lesions, it is possible to prevent morbidity and mortality by screening tests. Pap smear, colposcopy, and biopsy are among the main modalities in this regard, however there is no consensus on the diagnostic utility of the first 2 methods. This study sought to examine the diagnostic utility of Pap smear, colposcopy, and cytology in evaluating the non-benign cervical lesions. Materials and Methods: A cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…Incompatible with the findings of the present study, several studies have reported that the sensitivity of colposcopy is higher than that of Pap test for the detection of high-grade cervical lesions (1,22,24). In a study conducted in Yazd, Iran, the sensitivity of Pap smear and colposcopy was 50% and 80%, respectively, which is in contrast to our results (25).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Incompatible with the findings of the present study, several studies have reported that the sensitivity of colposcopy is higher than that of Pap test for the detection of high-grade cervical lesions (1,22,24). In a study conducted in Yazd, Iran, the sensitivity of Pap smear and colposcopy was 50% and 80%, respectively, which is in contrast to our results (25).…”
Section: Discussionsupporting
confidence: 61%
“…Cervical cancer is the fourth most frequent malignancy that affects women. The World Health Organization (WHO) estimates that 530,000 new cases of cervical cancer are diagnosed worldwide that lead to 275,000 death each year (1). Approximately 90% of deaths are reported from lowand middle-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical diagnosis is focused on the cellular morphological changes caused by HPV infection. The Papanicolaou test is considered the gold standard for early detection of cervical carcinoma, however, the Pap test results should not be considered to be a determinant criterion in the treatment decision (Sayyah-Melli et al, 2019;Kitchen & Cox, 2020). It is highly recommended that the cytological diagnosis via the Pap test be complemented with molecular HPV detection to increase the certainty of the diagnosis and maximize cancer prevention.…”
Section: Introductionmentioning
confidence: 99%